A Smart DNAzyme–MnO2 Nanosystem for Efficient Gene Silencing1. Issue 16 (26th February 2015) - Fan, Huanhuan; Zhao, Zilong; Yan, Guobei; Zhang, Xiaobing; Yang, Chao; Meng, Hongmin; Chen, Zhuo; Liu, Hui; Tan, Weihong
Abstract DNAzymes hold promise for gene‐silencing therapy, but the lack of sufficient cofactors in the cell cytoplasm, poor membrane permeability, and poor biostability have limited the use of DNAzymes in therapeutics. We report a DNAzyme–MnO2 nanosystem for gene‐silencing therapy. MnO2 nanosheets adsorb chlorin e6‐labelled DNAzymes (Ce6), protect them from enzymatic digestion, and efficiently deliver them into cells. The nanosystem can also inhibit 1O2 generation by Ce6 in the circulatory system. In the presence of intracellular glutathione (GSH), MnO2 is reduced to Mn2+ ions, which serve as cofactors of 10–23 DNAzyme for gene silencing. The release of Ce6 generates 1O2 for more efficient photodynamic therapy. The Mn2+ ions also enhance magnetic resonance contrast, providing GSH‐activated magnetic resonance imaging (MRI) of tumor cells. The integration of fluorescence recovery and MRI activation provides fluorescence/MRI bimodality for monitoring the delivery of DNAzymes.